American covenant national parks, their promise, and our nation's future - Soukup, Michael A., 1944-; Machlis, Gary E. (Yale University Press, 2021)
An intimate and candid account of our national parks and their strengths, vulnerabilities, and essential role in American life Part memoir, part critique, and paean to the value of national parks, American Covenant distills the experience and insights from two long careers in conservation. Michael A. Soukup and Gary E. Machlis show how the national parks are essential to maintaining the essence of our national heritage, and key to America's future in a changing climate and political landscape. Sharing real-world examples of both victories and defeats in protecting national parks, this candid, thoughtful book reminds us that the national parks are a promise--a covenant--within and between generations of Americans. The book is also a call to revitalize, reconstitute, reconfigure, and reform the National Park Service, which the authors believe is governed too much by outdated management practices and politics instead of a foundation of expertise and science